Needle knife-assisted polypectomy in hot snare-resistant fibrotic inflammatory polyps - Wu,Xian-rui (2014)
BACKGROUND: Inflammatory polyps are common sequelae in patients with inflammatory bowel diseases (IBD). Those polyps can usually be removed with snare polypectomy. There were limited data evaluating the management of hot snare-resistant inflammatory polyps.METHODS: We reported on two cases with hot snare-resistant inflammatory polyps, one was a Crohn's disease (CD) patient with the polyp at the ileo-colonic anastomosis (ICA) and the other one was an ulcerative colitis (UC) patient with polyp at the pouch inlet.RESULTS: Sedated endoscopy was performed, which showed a large 2.5 cm pedunculated polyp at the ICA in the first patient and a large 5 cm pedunculated polyp at the pouch inlet in the second patient. Hot snare polypectomy was initially attempted, but failed in both patients. Then endoscopic needle knife polypectomy was performed, which helped complete polypectomy. Both procedures took approximately 25 minutes each. The patients tolerated the procedure well and continued to do well after the procedure. The final pathological diagnoses for both patients were inflammatory polyps with extensive fibrosis.CONCLUSIONS: Endoscopic needle knife-assisted polypectomy appeared to be an effective technique for the management of hot snare-resistant inflammatory polyps.